The legend of Mahsuri case study on the perception among student of Faculty Art and Design (Graphic Design) in UiTM Kampus Bandaraya Melaka / Mohamad Zaimhairudin Sermi - Sermi, Mohamad Zaimhairudin (2014)
The legend of Mahsuri is the prototype tale of the virtuous wife who has been wronged by nobility, due to gossip, ill-will and the abuse of power. Up till the late-80s, it was said that the island of Langkawi was put under a curse for seven generations by Mahsuri, which is why it could never develop. This is the story that can give a lot of moralistic for people especially teenager and adult. But now days, they don't adapt about this moralistic story through their life and think this is just a myths for our culture. Although The legendary of Mahsuri is the one famous story in Malaysia, but now days it become slowly forgotten and disappear from the soul of our youth. Unfortunately, many people have a lot version of story about Mahsuri and that can make people especially student or youth generation become slowly untrust and forgotten about this legend. In their story, they specify on the superficial aspects, instead of functional and historical aspects of the legendary stories.It is the purpose of this paper to explore about perception and awamess people especially among student about The Legends of Mahsuri to prove that awareness about this legends slowly dissapears and forgotten and it will give some recommendation how to make The Legends of Mahsuri will not being forgotten for our next generation to make it always being reminder about this legendary.